Cover Image. Issue 3 (25th May 2020) - Pikalo, Jutta; Schoder, Marie‐Eve; Sehl, Julia; Breithaupt, Angele; Tignon, Maryléne; Cay, Ann Brigitte; Gager, Anna Maria; Fischer, Melina; Beer, Martin; Blome, Sandra
Abstract : The cover image is based on the Original Article The African swine fever virus isolate Belgium 2018/1 shows high virulence in European wild boar by Jutta Pikalo et al., https://doi.org/10.1111/tbed.13503 . Supported by Friedrich‐Loeffler‐Institute, TEM courtesy of Kati Franzke